Legal frameworks of organization and activity of international commercial arbitration (Journal of actual problems of jurisprudence, 2019)
This article deals with the role which plays an international commercial arbitration in resolving disputes arising in the sphere offoreign-economic activity.Specified legal base has been formed in Kazakhstan which provides resolving disputes by international commercial arbitration. Andalso legal nature of international commercial arbitration is defined here.